1990
DOI: 10.1002/path.1711620109
|View full text |Cite
|
Sign up to set email alerts
|

Silver stained nucleolar organizer region proteins (Ag‐NORs) as a predictor of prognosis in colonic cancer

Abstract: Using a one-step silver nitrate staining technique, routinely processed tumour tissues of 49 carcinomas of the colon were investigated to demonstrate silver-stained nucleoli (Ag-nus) and argyrophilic proteins associated with the so-called nucleolar organizer regions (Ag-NORs). Patients with attempted curative resections and tumour stages Dukes' A, B, C1 and C2, with an uneventful follow-up period of at least 48 months (N = 17), showed a statistically significant (P = 0.0001) lower mean number of scattered Ag-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
3

Year Published

1991
1991
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 15 publications
2
25
0
3
Order By: Relevance
“…Moreover, the uni-and multivariate survival analysis of the remaining 43 oro-hypopharyngeal carcinomas showed that AgNOR count was the only significant parameter. This result is in accordance with the data obtained in other types of tumours: childhood neuroblastomas (Egan et al, 1988b), prostatic cancer (Contractor et al, 1989) and colorectal carcinomas (Ofner et al, 1990;Ruschoff et al, 1990). The prognostic significance of AgNOR counts may be due to their correlation with cell proliferation: in non-Hodgkin's lymphoma (Hall et al, 1988) and breast carcinomas there is a clear correlation between AgNOR staining and Ki67 immunostaining; cells positive for Ki67 have high AgNOR counts, while Ki67 negative cells contain only one or two AgNORs (Murray et al, 1989); a linear relationship was found between cell duplication activity and the amount of AgNOR proteins in cell lines derived from different tumour types (Derenzini et al, 1990).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the uni-and multivariate survival analysis of the remaining 43 oro-hypopharyngeal carcinomas showed that AgNOR count was the only significant parameter. This result is in accordance with the data obtained in other types of tumours: childhood neuroblastomas (Egan et al, 1988b), prostatic cancer (Contractor et al, 1989) and colorectal carcinomas (Ofner et al, 1990;Ruschoff et al, 1990). The prognostic significance of AgNOR counts may be due to their correlation with cell proliferation: in non-Hodgkin's lymphoma (Hall et al, 1988) and breast carcinomas there is a clear correlation between AgNOR staining and Ki67 immunostaining; cells positive for Ki67 have high AgNOR counts, while Ki67 negative cells contain only one or two AgNORs (Murray et al, 1989); a linear relationship was found between cell duplication activity and the amount of AgNOR proteins in cell lines derived from different tumour types (Derenzini et al, 1990).…”
Section: Discussionsupporting
confidence: 91%
“…Small size, large number and scattered distribution of NORs are characteristic of malignant tumours; large size, small number and clustered distribution are characteristic of benign tumours (Crocker & Nar, 1987;Crocker & Skilbeck, 1987;Derenzini et al, 1988;Smith & Crocker, 1988). This technique allows also retrospective studies, as proteins associated with NORs can be detected by a simple one-step argyrophilic technique (AgNOR staining), even in routinely fixed and paraffin wax-embedded tissue sections (Ploton et al, 1986). Interest in this method has recently increased since a correlation between AgNOR content and prognosis has been observed in neuroblastoma (Egan et al, 1988b), prostatic cancer (Contractor et al, 1989), breast carcinomas (Sivridis & Sims, 1990) and colorectal carcinomas (Ofner et al, 1990;Riischoff et al, 1990).…”
mentioning
confidence: 99%
“…In colon tumours (Rushoff et al, 1990a;Ofner et al, 1990) and in renal cell tumours (Delahut et al, 1991). AgNORs have been able to predict survival significantly even within clinical stage categories (Delahut et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…including head and neck squamous cell carcinomas. have shown that the mAgNOR counts were higher in tumours with poor prognosis than in those with good prognosis (Contractor et al 1989: Ruschoff et al 1990: Ofner et al 1990: Kolar et al 1992: Delahunt et al 1993: Piffko et al 1997. With increasing mAgNOR counts.…”
mentioning
confidence: 99%